White House Budget Proposal Supports Science Agencies and Programs. (16th April 2013) - Showstack, Randy
Abstract : The proposed federal budget for fiscal year (FY) 2014, which the Obama administration sent to Congress on 10 April, would provide overall strong support for federal science agencies in a tight budget environment. The proposal calls for $142.8 billion for federal research and development (R&D), an increase of almost $1.9 billion, or 1.3%, above the 2012 enacted level in current dollars. However, the proposed budget is a slight decrease when factoring in an expected 4% inflation between 2012 and 2014.